Spontaneous perforation of common hepatic duct: an intraoperative surprise - Y. Kerkeni; F. Thamri; A. Zouaoui; B. Aziza; R. Jouini (SpringerOpen, 2022)
Abstract Background Pediatric spontaneous bile duct perforation is one of the rare causes of acute abdomen in infants. With a highly variable presentation, diagnosis and treatment can prove challenging. We report a case of spontaneous common hepatic duct perforation mistaken for appendicular peritonitis. Case presentation An otherwise healthy 3-year-old boy presented to the emergency department with complaints of abdominal pain, distention, bilious vomiting, and fever evolving for 4 days. Preoperative ultrasound was suggestive of appendicular peritonitis. Laparotomy revealed abundant biliary fluid, a distended gallbladder with thickened and inflammatory wall, and a macroscopically normal appendix. Intraoperative cholangiography showed a leak of contrast from the anterior wall of the common hepatic duct, 2-3 mm below the upper biliary confluence and 2 cm above the junction of the cystic duct to the common hepatic duct. A cholecystostomy was performed, and two external intraabdominal drains were placed. A retrograde cholangiogram was performed on postoperative day 21 showing no extravasation of contrast product. The patient was discharged on postoperative day 25. Conclusion Spontaneous perforation of the common hepatic duct is a rare phenomenon. It should be considered as a differential diagnosis in pediatric patients that present with unexplained peritonitis. The optimal method of diagnosis and management remains controversial.